US-Japan alliance and China's response. - Ng, David Choon Lee. (2008)
This study seeks to clarify China's strategic goals and challenges as may be discerned at this point in time, and see how they relate to China's response to the redefined US-Japan alliance. In the next section, the key aspects of the redefined alliance and revised guidelines will be discussed. This will lead on to an examination of the issues and challenges of China.